A Descriptive Study of Food Pantry Characteristics and Nutrition Policies in Maine. Issue 4 (3rd July 2020) - Joly, B.M.; Hansen, A.; Pratt, J.; Michael, D.; Shaffer, J.
ABSTRACT: Food pantries have the potential to promote nutrition through public health interventions and several novel approaches have been adopted. Prior to implementing new efforts, an important first step is understanding the receptivity and capacity of food pantries to adopt innovative strategies ultimately designed to improve health outcomes related to diet among the clients they serve. This is particularly important in rural areas, given the gap in research on several factors including food pantries' organizational capacity, operations, personnel, and interest in distributing nutritious foods. We conducted a descriptive study based on a survey administered to 274 food pantry directors in Maine, a largely rural state to learn about their experiences, perceptions, as well as their pantry's policies, practices, and capacity. Data were collected via an online 29-item questionnaire for those with email and through a paper and pencil version for those without email access. This study achieved a 69% response rate and the findings revealed variability in terms of practices, policy, capacity and food availability. Yet, despite these differences, respondents indicated a fairly consistent desire to provide balanced, nutritious meals. This suggests that pantry directors in Maine recognize the need for nutritious food and may be willing to adopt nutrition interventions.